Increased Circulating Levels of Interleukin-6 Induce Perturbation in Redox-Regulated Signaling Cascades in Muscle of Dystrophic Mice. (6th August 2017) - Pelosi, Laura; Forcina, Laura; Nicoletti, Carmine; Scicchitano, Bianca Maria; Musarò, Antonio
Abstract : Duchenne muscular dystrophy (DMD) is an X-linked genetic disease in which dystrophin gene is mutated, resulting in dysfunctional or absent dystrophin protein. The pathology of dystrophic muscle includes degeneration, necrosis with inflammatory cell invasion, regeneration, and fibrous and fatty changes. Nevertheless, the mechanisms by which the absence of dystrophin leads to muscle degeneration remain to be fully elucidated. An imbalance between oxidant and antioxidant systems has been proposed as a secondary effect of DMD. However, the significance and precise extent of the perturbation in redox signaling cascades is poorly understood. We report that mdx dystrophic mice are able to activate a compensatory antioxidant response at the presymptomatic stage of the disease. In contrast, increased circulating levels of IL-6 perturb the redox signaling cascade, even prior to the necrotic stage, leading to severe features and progressive nature of muscular dystrophy.